The Influence of Adversity Quotient, Achievement Motivation, and Self-Concept on Learning Independence - Melati, Elvina Reza; Naufalin, Lina Rifda; Mulasiwi, Cut Misni (Journal of Economics Education and Entrepreneurship, 2025)
This study is quantitative research conducted to analyze the influence of adversity quotient, achievement motivation, and self-concept on learning independence. The population in this study consisted of 196 students from Economic Education Study Program at Jenderal Soedirman University, from the 2021, 2022, and 2023 cohorts with a sample of 132 students. The data used in this research were obtained using a closed-ended questionnaire with proportionate stratified random sampling as the sampling technique and multiple linear regression analysis as the data analysis technique. The results of the research and data analysis using the SPSS program showed that: (1) There is no positive influence of adversity quotient on learning independence. (2) There is a positive influence of achievement motivation on learning independence. (3) There is a positive influence of self-concept on learning independence. The implications of this research are that students are advised to enhance their learning independence by increasing motivation to achieve better academic performance and to enhance their self-concept by nurturing a positive view of themselves, thereby developing self-confidence.